2001
DOI: 10.1051/0004-6361:20011354
|View full text |Cite
|
Sign up to set email alerts
|

Hot halo gas in the Virgo cluster galaxy NGC 4569

Abstract: Abstract.We have observed the Virgo cluster spiral NGC 4569 in X-rays with ROSAT (0.1-2.4 keV) and in the optical. From the PSPC image one can distinguish different components, like the dominant source in the nuclear region, the galactic disk, and a diffuse soft component extended to the west. This latter one coincides with a giant Hα structure. In both spectral ranges the structure reaches up to 9 kpc out of the disk. This coincidence, the soft X-ray energy distribution, and the existence of a central starbur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 55 publications
(71 reference statements)
1
42
0
Order By: Relevance
“…Rosat, XMM-Newton, Chandra X-ray, and VLA 1.4, 4.86 GHz radio continuum images of NGC 4569 show extended features that are perpendicular to the stellar disc of the galaxy (Tschoeke et al 2001;Chyzy et al 2006;Grier et al 2011;Wezgowiec et al 2011Wezgowiec et al , 2012. The extension of the hot gas traced by the 0.2−1 keV XMM-Newton X-ray image, however, is smaller than that of the ionized gas (Figs.…”
Section: Comparison With Multifrequency Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Rosat, XMM-Newton, Chandra X-ray, and VLA 1.4, 4.86 GHz radio continuum images of NGC 4569 show extended features that are perpendicular to the stellar disc of the galaxy (Tschoeke et al 2001;Chyzy et al 2006;Grier et al 2011;Wezgowiec et al 2011Wezgowiec et al , 2012. The extension of the hot gas traced by the 0.2−1 keV XMM-Newton X-ray image, however, is smaller than that of the ionized gas (Figs.…”
Section: Comparison With Multifrequency Datamentioning
confidence: 99%
“…The spur of gas observed on the western side has a higher recessional velocity with respect to the nucleus of the galaxy and is thus an outflow. The nuclear outflow is probably powered by a nuclear starburst (Barth et al 1998;Maoz et al 1998;Barth & Shields 2000;Tschoeke et al 2001;Chyzy et al 2006). The spectral synthesis analysis of the nuclear HST spectra carried out by Barth & Shields (2000), who classified it as a typical LINER/HII transition nucleus, date the nuclear ( < ∼ 30 pc) starburst as ∼3−6 Myr (Barth & Shields 2000;Gabel & Bruhweiler 2002).…”
Section: The Nuclear Outflowmentioning
confidence: 99%
See 1 more Smart Citation
“…On larger scales Tschöke et al (2001) detected a large soft X-ray emitting region above the disk of NGC 4569 which implies a large energy input into the halo. Hensler et al (2003) reported on a bipolar outflow seen in X-rays and a giant outflow (∼10 kpc in length) to the western side of the galaxy in Hα (see also Bomans et al 2007, submitted).…”
Section: Introductionmentioning
confidence: 98%
“…The presence of a supergiant-dominated starburst was established by Keel (1996). Barth & Shields (2000) demonstrated that a starburst with a large population of very hot Wolf-Rayet stars could produce the observed spectrum of the nucleus and AGN activity is ruled out by X-ray (Terashima et al 2000;Tschöke et al 2001;Ho et al 2001) and radio observations (Hummel et al 1987;Neff & Hutchings 1992). Gabel & Bruhweiler (2002) showed that for the starburst to be the only source of photoionization (no AGN) extreme conditions are required, with ∼5 × 10 4 O and B stars squeezed into the inner 30 pc.…”
Section: Introductionmentioning
confidence: 99%